ANALISIS TINGKAT PEMAHAMAN PESERTA DIKLAT TERHADAP TUGAS ONLINE PADA DIKLAT PENINGKATAN KAPASITAS FORECASTER METEOROLOGI - Sulistya, Widada (Jurnal Widya Climago, 2020)
BMKG Education and Training Centre has the task and function to organizing education and training activities. BMKG ETC is also obliged to implement a policy of distance learning activities during covid -19 pandemic. All series of activities related to learning programs are delivered by online. The success of communication can be measured by how far the other people understand what the communicator says. One of the goals of communication is to influence other people to do what we expect. This study will be conducted to measure the level of understanding of training participants on online studies. This study is a quasi-experimental study. Primary data based on the survey of the training participants. The number of training participants was 31 people, who comesfrom the BMKG Stations throughout Indonesia. Based on the analysis of each case, it shows that the case of suggestions for improving the issue of weather early warnings, was the best understand by respondents, because 100% of respondents are good and very good classification. Meanwhile, for the case of constraints on the issue of weather early warning were in the second place with 95% of respondents in the good and very good classification, while the remaining 5% were classified as sufficient. The discussion of the operational situation before training can be used as an inventory of operational problems, then based on these problems, the training participants can discussion to solve operational problems with the managements during the class.